DETERMINANTS OF INSTITUTIONAL TRUST IN TRANSITION ECONOMIES: LESSONS FROM SERBIA - Džunić, Marija; Golubović, Nataša; Marinković, Srđan (Economic Annals, 2020)
This study aims to provide evi-dence on the drivers of institutional trust in transition economies. Trust in institutions is of critical importance for the consolidation of democracy, as well as for political and social stability. Bearing in mind the political devel-opments during the transition, the fragile de-mocracies of post-socialist countries have faced significant challenges in terms of declining in-stitutional trust, leading to problems of legiti-macy and government ineffectiveness. There-fore, the transition countries represent a fertile ground for testing the theories that explain the origins and dynamics of institutional trust. In this paper we explore the level of institutional trust in Serbia and test the alternative views on the determinants of trust in key institutions of cultural and institutional theories. The cultural perspective implies that the level of trust in in-stitutions is dependent on citizens’ long-stand-ing and deep-seated cultural norms, while the institutional approach explains trust as the out-come of individual perceptions of institutional performance. In order to examine the cultural and institutional variables that explain trust in a set of public institutions in Serbia, we employ individual-level data from the Life in Transi-tion Survey. The analysis is aimed at generating policy suggestions and measures that can raise institutional credibility.